Irregular structures of the F layer at high latitudes during ionospheric heating. - Rietveld, Michael T.; Tereshchenko, E.D.; Kozlova, M.O.; Brekke, Asgeir; Evstafiev, O.V.; Khudukon, B.Z.; Nygren, T. (European Geophysical Society, 2000)
Results on heating the ionospheric F region above Tromsø, Norway are presented. The ionosphere was monitored by satellite tomography and amplitude scintillation methods as well as the EISCAT incoherent scatter radar. No effect of heating was observed in the daytime. In the evening and in the pre-midnight sector, noticeable tilts of the F region were observed during heating periods. The tilts overlapped the heating cone, where the electron density decreased and irregularities exceeding 10 km in size appeared. Between the heating periods the F layer was restored to its horizontal shape. The anisotropic parameters of small-scale irregularities with scale lengths of hundreds of metres were also determined. It was found that the perpendicular anisotropy points in the direction of F region plasma flow. In some cases the results can be explained by assuming that the small-scale irregularities were generated within the heating cone and drifted out of the heating region where they were subsequently observed.